1999
DOI: 10.1073/pnas.96.9.5194
|View full text |Cite
|
Sign up to set email alerts
|

Protein conjugates of synthetic saccharides elicit higher levels of serum IgG lipopolysaccharide antibodies in mice than do those of the O-specific polysaccharide fromShigella dysenteriaetype 1

Abstract: Our development of vaccines to prevent shigellosis is based on the hypothesis that a critical ( The average molar ratios of the saccharides to HSA ranged from 4 to 24. Serum IgG anti-LPS, elicited in mice by O-SP-HSA or synthetic tetra-, octa-, dodeca-, and hexadecasaccharide fragments, was measured by ELISA. Outbred 6-week-old female mice were injected s.c. three times at biweekly intervals with 2.5 g of saccharide as a conjugate and were bled 7 days after the second and third injections. Excepting the tetram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
128
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 169 publications
(139 citation statements)
references
References 36 publications
8
128
1
Order By: Relevance
“…Rha repeating unit bound at their reducing end to a carrier protein by single point attachment (12). We showed that the synthetic oligosaccharide-protein conjugates induced higher antibody levels than the conjugates of the native O-SP.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Rha repeating unit bound at their reducing end to a carrier protein by single point attachment (12). We showed that the synthetic oligosaccharide-protein conjugates induced higher antibody levels than the conjugates of the native O-SP.…”
Section: Resultsmentioning
confidence: 85%
“…We have mapped the effects of the oligosaccharide length and the number of saccharide chains per protein (density) on the immunogenicity of conjugates. A maximal O-SP antibody response was observed with conjugates of four repeating units and Ϸ10 chains per human serum albumin (12).…”
mentioning
confidence: 88%
“…Evaluation of such conjugates in children showed age-related antibody responses and protection (7). A significant improvement in the immunogenicity of S. dysenteriae type 1 conjugates was achieved by using synthetic oligosaccharides (OS) of defined lengths bound by their reducing ends to a protein at defined densities (8). Synthesis of S. sonnei O-SP oligosaccharides has not been possible to date.…”
mentioning
confidence: 99%
“…The choice of conjugation methods is restricted by the pH and temperature sensitivities of both vaccine components. The types of chemical linkages between the O-SP and the protein as well as the saccharide chain length and the chain density on the protein were shown to influence the serum antibody responses to both vaccine components [35,36,37,38,39,40]. Here we studied two conjugation methods of O-SP either by their Kdo or their glucosamine residues.…”
Section: Discussionmentioning
confidence: 99%